2011
DOI: 10.1007/s11605-011-1418-9
|View full text |Cite
|
Sign up to set email alerts
|

Mir-148a Improves Response to Chemotherapy in Sensitive and Resistant Oesophageal Adenocarcinoma and Squamous Cell Carcinoma Cells

Abstract: MiR-148a sensitized chemotherapy-sensitive oesophageal cancer cell lines to cisplatin and, to a lesser extent, to 5-flurouracil and attenuated resistance in chemotherapy-resistant variants. Further experimental and clinical studies to investigate the exact mechanisms involved are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 47 publications
2
82
0
Order By: Relevance
“…Increases in sample size, increase the likelihood of observing differences in expression. Recent studies have shown that miR-148a expression levels are significantly associated with differentiation grade (33) lymph node metastasis (34), and drug resistance in several cancers (35,36). Therefore, we next analyzed the relationship between miR-148a and clinicopathological characteristics in ovarian cancer, including chemotherapy prognosis and survival time.…”
Section: Mir-152 and Mir-148a Have No Effect On Invasion Of Skov3 Cellsmentioning
confidence: 99%
“…Increases in sample size, increase the likelihood of observing differences in expression. Recent studies have shown that miR-148a expression levels are significantly associated with differentiation grade (33) lymph node metastasis (34), and drug resistance in several cancers (35,36). Therefore, we next analyzed the relationship between miR-148a and clinicopathological characteristics in ovarian cancer, including chemotherapy prognosis and survival time.…”
Section: Mir-152 and Mir-148a Have No Effect On Invasion Of Skov3 Cellsmentioning
confidence: 99%
“…Noteworthy, although there are no reports regarding the role of miR-148a in NSCLC, miR-148a may prove a novel Rh2 target in NSCLC. miR-148a was originally shown to be downregulated in human breast cancer; however, it is associated with improved response to chemotherapy in esophageal cancer cell lines, attenuates paclitaxel-resistance of hormonerefractory, drug-resistant prostate cancer PC3 cells, suppresses gastric cancer cell invasion and metastasis, and promotes apoptosis in colorectal cancer cells (20)(21)(22)(23)(24). Therefore, future studies should be directed towards elucidating the relationship between Rh2-mediated anticancer properties and miR-148a upregulation in NSCLC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that HLA-G expression level may be regulated by miR-148a, and that miR-148b and HLA-G were upregulated in primary ESCC tissues (13,16). Based on these reports, it was hypothesized that miR-148a may contribute to the proliferation of ESCC cells by regulating HLA-G expression.…”
Section: Effect Of Mir-148a On Hla-g Expressionmentioning
confidence: 99%
“…Hummel et al (15) reported that miR-148a was downregulated in patients with recurrent EC. They also demonstrated that in EC cell lines, upregulation of miR-148a improved sensitivity to chemotherapy (16). However, whether miR-148a is downregulated in primary ESCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%